SCARA Robot Optimal Trajectory Planning for Pick and Place Tasks - دبور عبد الرزاق (Latakia University Journal -Engineering Sciences Series, 2021)
The processes of picking and placing objects are among the most widespread industrial operations and the most demanding to move the objects with the least possible time and the least dynamic forces affecting the robot and the body. In this paper, multi trajectories were designed for pick and place task using SCARA robot, these trajectories were compared using linear acceleration values for robot’s tool, robot joint’s angular velocity and robot joint’s angular acceleration. In this paper, traditional trajectory, modified trapezoid curve and modified trapezoid curve with radius equal height were compared using solidworks software in robot designing and simulation and finding linear acceleration for robot’s tool, robot joint’s angular velocity and robot joint’s angular acceleration. The results showed a significant superiority of the modified trapezoid curve with radius equal height to the rest of tested trajectories, as this trajectory led to a decrease in angular velocities values by ( ) for first joint and by ( ) for second joint compared with traditional trajectory, It also reduced the highest value of angular acceleration by ( ) for first joint and by ( ) for second joint compared with traditional trajectory, in addition the linear acceleration value for robot’s tool was reduced by ( ) compared with traditional trajectory. The modified trapezoid curve with radius equal height path shows significant superiority of modified trapezoid curve tested paths, as this trajectory led to a decrease in angular velocities and accelerations values for robot joints, in addition the linear acceleration value for robot’s tool was reduced compared with modified trapezoid curve with various radius.